European guidelines for quality assurance in colorectal cancer screening and diagnosis. First Edition – Annotations of colorectal lesions - Michael Vieth; Philip Quirke; R. Lambert; Lawrence von Karsa; Mauro Risio (2012)
Multidisciplinary, evidence-based guidelines for quality assurance in colorectal cancer screening and diagnosis have been developed by experts in a project coordinated by the International Agency for Research on Cancer. The full guideline document covers the entire process of population-based screening. It consists of 10 chapters and over 250 recommendations, graded according to the strength of the recommendation and the supporting evidence. The 450-page guidelines and the extensive evidence base have been published by the European Commission. The chapter on quality assurance in pathology was supplemented by an annex describing in greater detail some issues raised in the chapter, particularly details of special interest to pathologists. The content of the annex is presented here to promote international discussion and collaboration by making the issues discussed in the guidelines known to a wider professional and scientific community.